Housing and utility complex in the system of sociocultural institutionality - B. Y. Ashinov; A. M. Siyukhova (Вестник Майкопского государственного технологического университета)
The article examines the issue of the housing and utility services as a sociocultural institution. It has been noted that the larger the urban settlement, the more difﬁcult it is to organize orderly interactions necessary for the sustainability of the urban structure, convenience for residents, safety, expressiveness of the cultural landscape, etc. Housing and utility services perform an important function of forming a positive image of a city, making it competitive in attractiveness in comparison with others cities. The research problem lies in the fact that the housing and utility services are generally considered from the standpoint of economics and management, despite the fact that the activities of this complex have a pronounced socio-cultural orientation. This allows us to talk about the relevance of the study of housing and utility services as a sociocultural institution in order to identify factors that contribute to the effectiveness of the activities of public utility organizations, or lead to institutional dysfunctions. The main research method chosen is structural and functional analysis, which allows us to consider housing and communal services from the point of view of the implementation of sociocultural functions and the search for the causes of possible dysfunctions. Consistently the institutional features of housing and utility complex are revealed. In conclusion, the main reasons for possible institutional dysfunctions of the object under consideration have been determined: violations of functionality are possible, ﬁrstly, as a result of general crisis conditions in the economy and politics; secondly, as a result of natural disasters; thirdly, as a result of a lack of understanding of the importance and complexity of housing and communal services by state and municipal authorities. Also, the gap in this area may be affected by shortcomings in the organizational culture of speciﬁc enterprises in the public utilities sector.